BLIS Fingerprinting as a Tool to Investigate the Distribution and Significance of Bacteriocin Production and Immunity in Streptococcus pyogenes and Streptococcus salivarius - John R. Tagg; John D. F. Hale; Liam K. Harold (Applied Microbiology)
The study of bacteriocins has significantly enhanced our understanding of microbial interactions, notably within the genus Streptococcus. Among the most functionally diverse and clinically relevant bacteriocins are those belonging to the lantibiotic class, which exhibit potent antimicrobial properties and are central to the competitive dynamics of streptococcal species. This review focuses on the discovery and characterization of bacteriocins produced by Streptococcus pyogenes and Streptococcus salivarius, emphasizing their biological significance within their exclusive human host. A cornerstone of these studies has been the development and application of the pioneer agar culture-based bacteriocin detection methodology, known as streptococcal bacteriocin fingerprinting. This approach has proven invaluable for the initial detection and differentiation of a wide array of bacteriocin-like inhibitory substances (BLIS) in streptococcal populations. A central theme of this review is the diverse biological roles of lantibiotics in S. pyogenes and S. salivarius, particularly in relation to microbial competition, colonization dynamics, and host interactions. The expression of lantibiotic determinants provides distinct advantages to the producing strain, including enhanced niche establishment and the ability to suppress competing microbes. Furthermore, the presence of specific lantibiotic immunity mechanisms safeguards the producer from self-inhibition and potential antagonism from closely related competitors. In S. pyogenes, lantibiotic production has been implicated in virulence modulation, raising important questions about its role in pathogenicity and host immune evasion. Conversely, S. salivarius, a prominent commensal and probiotic candidate species, utilizes its lantibiotic arsenal to confer colonization benefits and mediate beneficial interactions, especially within the oral and upper respiratory tract microbiomes. The implications of in situ lantibiotic expression extend beyond microbial ecology, presenting opportunities for innovative probiotic and therapeutic applications. The potential for harnessing bacteriocin-producing streptococci in antimicrobial interventions, particularly in combating antibiotic-resistant pathogens, underscores the translational relevance of these findings. This review integrates historical and contemporary perspectives on streptococcal bacteriocin research, providing insights into future avenues for leveraging these bioactive peptides in clinical and biotechnological contexts.